Application of blockchain in the cluster of unmanned aerial vehicles. Issue 1 (10th May 2021) - Chen, Shiwu; Li, Qin; Wang, Wei; Yang, Yu; Jiang, Jun
Abstract: With the considerable exploration of unmanned aerial vehicles in civilian and military fields, the data storage and transmission mechanism of unmanned aerial vehicles exhibit significant security limitations, which cannot meet the strict requirements for data security in civilian and military business scenarios. In recent years, blockchain technology has been tried to be applied to multiple fields. The features of blockchain includes decentralization, immutability, transparency and auditability, make transactions more secure and tamper proof. In view of the many excellent features of blockchain, in this paper, blockchain technology is introduced into the application of cluster of unmanned aerial vehicles, aiming to solve the problems of identity authentication, secure and reliable transmission of data between unmanned aerial vehicles, and access control of the data on the blockchain, thereby to enhance the security of the cluster of unmanned aerial vehicles and to ensure the integrity and security of data.